Komitmen, Kecerdasan Emosional, dan Budaya Organisasi Terhadap Organizational Citizenship Behavior (OCB) PAUD-SD Islam Makarima Kartasura - Setyaningsih, Yayuk; Istiatin, Istiatin; Suryo, Ibnu (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to recognize determine the effectoof commitment, emotionalIintelligence, and organizational culture on organizational citizenship behavior (OCB). Object of this research was the teacher and staff of Makarima Kartasura Islamic PAUD- SD. Population was drawn from the whole employees of the 55 people. Saturated sampling is the sampling technique used. Questionnaire is the method used to collect data. Multiple regression analysis is the data analysis technique employed. The result showed that partially the commitment|had significant effect on the organizational citizenship behavior of Makarima Kartasura Islamic PAUD- SD, emotional intelligence has a significant effectoon the organizationallcitizenship behavior (OCB) of Makarima Kartasura Islamic PAUD- SD, organizational culture has a significant effect on the organization citizenship behavior (OCB) of Makarima Kartasura Islamic PAUD- SD. The result of the Adjusted R2 has coefficient 36,6 %, indicated that organizational citizenship behavior in the Makarima Kartasura Islamic PAUD- SD is influenced by Commitment, emotional intelligence, andiorganizational culture. While thei remaining 63,4 % is explained byiother variables. Keywords: Commitment, Emotional Intelligence, Organizational Culture, OCB